Detection and strain identification of Actinobacillus actinomycetemcomitans by nested PCR. - Leys, E J (1994)
By using PCR, Actinobacillus actinomycetemcomitans strains were identified directly from plaque samples without the need to isolate or culture bacteria. DNA fragments were generated by a nested, two-step PCR amplification of the ribosomal spacer region between the 16S and 23S rRNA genes. For the first amplification, primers homologous to sequences common to all bacterial species were used. This was followed by a second amplification with primers specific to A. actinomycetemcomitans. The ribosomal DNA spacer region was amplified from as few as 10 bacterial cells within a total population of 10(8) cells (0.00001%), and cross-reactivity between species was not observed. DNA fragments specific for Porphyromonas gingivalis were generated from the same samples by using a P. gingivalis-specific primer, and equivalent sensitivity and specificity were observed. A. actinomycetemcomitans was detected in 60% and P. gingivalis was detected in 79% of 52 subjects tested. Sequence analysis of the spacer region DNA fragment for A. actinomycetemcomitans gave precise strain identification, producing unique sequences for seven reference strains and identification of nine plaque-derived isolates. A phylogenetic tree based on quantitative sequence relationships was constructed. Two-step PCR amplification directly from plaque samples combined with sequence analysis of the ribosomal DNA spacer region provides a sensitive assay for detection and strain identification of multiple species directly from a single plaque sample. This simplified approach provides a practical method for large-scale studies on the transmission and pathogenicity of periodontitis-associated bacteria.